Exploring the effects of various types of stressors on the physical and mental health symptoms of police officers in South Korea. (December 2021) - Cho, Joon Tag; Park, Jisun
Abstract: This study compared the stress levels and physical and mental health symptoms of patrol officers and emergency dispatch officers in South Korea. We further explored stressors affecting the physical and mental health of police officers. Survey data were obtained from 254 patrol officers and 177 emergency dispatch officers working in Seoul. The average stress level exerted by the stressors was compared between groups, with consideration given to the characteristics of emergency calls. Logistic regression analysis was applied to determine the effects of the stressors on police officers' physical and mental health symptoms. Stress related to organizational management had the highest impact on physical and mental health, and differences in the stressors affecting the two group's physical and mental health were found. The results suggest that strategies reflecting the respective division stressors and characteristics are necessary. Furthermore, police officers' stress levels must be closely monitored and reduced through stress management programs.